A laboratory manual of neuroanatomy - Yew, D. T. W. (David T. W.) (World Scientific, 1986)
This manual guides the student through an organised regional study of the human brain proceeding from caudal to rostal direction. Different parts of the brain are described both on a gross and light microscopic level. The important structures of each brain region are emphasized not only in the text but also in the accompanying micrographs and line drawings. Where appropriate, the text also describes the histological organisation of the brain. A series of CAT scan pictures has also been included as an exercise for the students to correlate their knowledge on brain with X-ray images. This manual would serve as a foundation for necessary and practical information for future clinical years.